Epidemiology in sailing: A systematic literature review including suggestions for injury prevention - Amelie Johanna Sigge; Eva Maria Weingartmair; Elena Pocecco (Bern Open Publishing, 2024)
Introduction & Purpose Sailing is enjoyed by millions of people worldwide and as varied as the disciplines in sailing are the injuries. According to the definition of Neville and Folland (2009, p. 141), sailing injuries can be defined as "any physical complaint sustained by a sailor that results from sailing or sailing-related activities", whereby sailing-related illnesses have been excluded from this review. Most of the literature focuses separately either on elite sailing, recreational sailing, or offshore circumnavigations. This systematic literature review, in contrast, aimed to combine all these different types of sailing. The aim of this study was, thus, 1) to highlight the frequencies, types, locations, and causes of injuries in sailing, and 2) to summarize possible preventive measures. Methods Following the PRISMA guidelines, a literature search limited to research published from 01.01.2005 to 10.05.2024 was performed electronically in the databases PubMed and Cochrane Library using the keywords "sailing" AND "injuries". Exclusion criteria were non-English language and literature reviews. The literature search resulted in a total of 132 publications, thereof 112 were excluded based on their title, which was either double, not related to the disciplines of sailing or the topic of injuries. The remaining 20 publications were screened based on their abstracts. In this second round of filtering, 10 publications were excluded as they were not related to the disciplines of sailing and the topic of injuries. Finally, 10 publications were included in the present review. The selected literature was screened for the five categories of injury frequencies, types, locations, causes, and preventive measures associated with sailing. Results Injury frequency including time loss injuries and fatalities In general, sailing-related injury rates vary strongly from 0.59 to 16 per 1,000 hours of sailing (Feletti et al., 2021; Neville et al., 2006; Tan et al., 2016). Thereby, sailing was ranked among the safest sports in the Olympic Games 2008; moreover, in the Olympics 2012, 1.0% of sailors sustained an injury resulting in time loss (Ryan et al., 2016). No differences in the injury rate between sexes could be observed (Crunkhorn et al., 2022). The calculated fatality rate amounts to 1.19 deaths per million sailing days (Ryan et al., 2016). Injury types and locations In sailing, the most commonly injured body parts are the upper limbs (40% of all reported sailing injuries), followed by the spine, back, neck, and head (14-30%) and the lower limbs (10-27%) (Feletti et al., 2021; Ham & Jee, 2016; Hayes et al., 2023; Landsberg & Hunt, 2023; Nathanson et al., 2010; Neville et al., 2006). The most frequently reported injuries are mild injuries such as contusions (27-40%), lacerations (19%), and abrasions (11%), which can potentially occur on the hand, shoulder, arm, knee, foot, and ankle (Feletti et al., 2021; Forycka et al., 2023; Hayes et al., 2023) as well as muscle cramps/spasms (20%) and strains/sprains (13%; Tan et al., 2016). Also, sunburns are highly frequent with 16% of all surveyed cases (Nathanson et al., 2010). Moreover, in professional sailing, overuse injuries are accountable for 24-58% of all reported injuries and primarily affect joints and ligaments (Neville et al., 2006; Tan et al., 2016). Furthermore, severe injury types include fractures (25%), torn tendons/cartilage (16%), and brain concussion (14%; Nathanson et al., 2010). Injury risks and causes Injuries sustained during sailing can be attributed to extrinsic as well as intrinsic risk factors. Some of the most commonly identified extrinsic causes are related to environmental conditions, such as heavy weather and solar exposure (Hayes et al., 2023; Nathanson et al., 2010; Ryan et al., 2016). Further, lack of protective equipment and material failure (Nathanson et al., 2010; Ryan et al., 2016) as well as impacts with part of the boat, in particular the boom, (Forycka et al., 2023; Landsberg & Hunt, 2023; Tan et al., 2016) pose major causes of injuries. Hayes et al. (2023) found that smaller boat sizes are related to a higher rate of incidents. Intrinsic risk factors include sailors' inattentiveness, lack of communication among crew members, inadequate physical fitness, sleep deprivation, and insufficient experience (Forycka et al., 2023; Ham & Jee, 2016; Nathanson et al., 2010; Ryan et al., 2016). Nevertheless, a low level of sailing credentials was not found to increase the injury risk (Hayes et al., 2023). Additionally, different repetitive tasks contribute to overuse injuries (Neville et al., 2006). Moreover, alcohol consumption has been shown to play a role in 12.2% of sailing-related deaths (Ryan et al., 2016). Finally, the most common fatal incidents are due to collisions, grounding, and falling overboard (Ryan et al., 2016). Thereby, 81.6% of deaths can be linked to not wearing a life jacket (Ryan et al., 2016). Preventive measures To prevent injuries, (UV-)protective equipment, such as gloves, helmets, shoes, insulating cloths, hats, sunglasses, and sunscreen, should be used (Feletti et al., 2021; Nathanson et al., 2010). As the likelihood of accidents rises with shorter boat sizes, Hayes et al. (2023) recommended increasing the minimum boat length. Besides, ergonomic boat design needs to be applied (Nathanson et al., 2010). To prevent accidents, gaining confidence with the boat is paramount (Hayes et al., 2023). In addition, physical training needs to be included in the sailing routine at all levels (Feletti et al., 2021; Ham & Jee, 2016). Furthermore, sufficient sleep and distraction limitation should be ensured (Forycka et al., 2023). Feletti et al. (2021) suggested regularly changing the ropes to maintain a soft structure. Mandatory first aid training and equipment are further fundamental preventive measures (Forycka et al., 2023; Hayes et al., 2023; Landsberg & Hunt, 2023). Moreover, the prohibition of being intoxicated should be extended to passengers (Ryan et al., 2016). Finally, sailors should be convinced to wear life jackets, which can be facilitated by improving their comfort and aesthetics (Nathanson et al., 2010). Educational campaigns should foster these safety habits continuously (Nathanson et al., 2010). Discussion The results demonstrate a strongly varying injury rate of 0.59 to 16 per 1,000 hours of sailing (Feletti et al., 2021; Neville et al., 2006; Tan et al., 2016), which was found to be lower than in contact team sports, such as soccer, but similar to the incidence reported in non-contact sports, such as professional cricket (Neville et al., 2006). The calculated fatality rate of 1.19 deaths per million sailing days is comparable to the fatality rate in alpine skiing (Ryan et al., 2016). The presented risk factors lead to the suggestion of various preventive measures. Several of them, inter alia sun-protective behaviour, promotion of safety gear, coaching on proper sailing technique, physical training as well as first-aid education and equipment are deemed to be advantageous (Nathanson et al., 2010; Neville et al., 2006). However, it is questionable if other identified prevention steps, like increasing the boat size (Hayes et al., 2023) or frequently renewing the ropes (Feletti et al., 2021), automatically represent safety enhancements as the associated increase in boat weight and rope slipperiness could impair boat handling. Conclusion The present literature examination updates characteristics as well as possible risk factors for injuries in all sailing disciplines and summarizes related potential preventive measures. Further research should systematically assess the effectiveness of the different prevention options suggested. To increase safety within the sailing disciplines, the vigorous implementation of such preventive measures on the part of sailing federations seems to be of uttermost importance. References Crunkhorn, M. L., Wolff, A., Drew, M., Witchalls, J., Lalor, B., & Toohey, L. A. (2022). Establishing the incidence and prevalence of injury and illness in Australian sailing athletes over a full year of training and competition to help determine prevention priorities. Journal of Science and Medicine in Sport, 25(9), 726-731. https://doi.org/10.1016/j.jsams.2022.06.012 Feletti, F., Brymer, E., Bonato, M., & Aliverti, A. (2021). Injuries and illnesses related to dinghy-sailing on hydrofoiling boats.